To find the derivative of (3tan^(-1)square root(x)).
We know that d/dx(f(U(x))) ={ d/dUf(U)} = d/dx f(U)]*d/dx(U(x)).....(1)
(d/dx)(x^n) = nx^(n-1)........................................(2)
(d/dx)tan inverse x = 1/(1+x^2).............................(3)
d/dx[k*f(x)] = k* d/dx (f(x) or kf'(x)......................(4), where k is a constant.
We use the above in finding the derivative of the given expression.
Let y = (3tan^(-1)square root(x)) or
y=3 f(u(x)) .........................................................(5), where f(u) tan inverse u and u(x) = sqrtx = x^(1/2).
Therefore,
dy/dx=d/dx{3f(u(x)} = 3*d/dx{f(U) * d/dx(u(x)
=3 {1/(1+U^2)} ((1/2) x^(1/2 -1))
=3/(1+(sqrtx)^2) }(1/2)x^(-1/2)
=3/{2(1+x)x^(1/2)}
No comments:
Post a Comment